Maintenance management: A case study at UiTM Pulau Pinang / Nadira Ahzahar, Hazrina Ahmad and Siti Hafizan Hassan - Ahzahar, Nadira; Ahmad, Hazrina; Hassan, Siti Hafizan (2009)
Maintenance is an important element in the building process in order to ensure building will stand for longer periods. The effectiveness of building is not only being measured by its aesthetic values but how it would serve the required functions for better performance. Therefore, maintenance can be considered as a combination of several action carried out in an orderly manner to repair, service or replace the components of numerous equipment in a plant or a system such that they continue to operate for a specified time period. The aim of this study is to investigate the level of user’s satisfaction on contractor performance in maintenance works in UiTM Pulau Pinang. The finding of this study shows 70% of respondents in UiTM Pulau Pinang were satisfied with the level of contractor performance on maintenance work. This study is also highlights the common maintenance problems occurred at UiTM Pulau Pinang and rated according to its frequencies. The common damages classified under civil maintenance are floor cracking, broken flushing cistern, and wall cracking. The common problems classified under mechanical maintenance are lifting problem, air-conditioning problem and water supply problem. While common problems classified under electrical maintenance are switch port problem, socket port problem and lighting problem. From this study, it can be concluded that building and facilities conditions in UiTM Pulau Pinang is convenience and operating efficiently. Some recommendations have been given to improve the overall maintenance management system in UiTM Pulau Pinang.